Case Study : SN Kekal Maju Enterprise / Lyana Ibrahim - Ibrahim, Lyana (2020)
SN Kekal Maju Enterprise is one of the companies that deliver products and services related to pallets either wooden or plastics. This company was founded in 2016 by Mr. Samsul with registration number, SA0082151-D. It is based in Rantau Panjang, Klang, Selangor. After being operated in 4 years, this company had developed well and owned a building with 140 ft x 50 ft large. SN Kekal Maju Enterprise realized the importance of constantly updating their strategy to remain competitive in the market during this rapidly changing industry. Therefore, they used to inspire by their main mission when making any decision which is to provide their customers with the highest quality of products and services.